Itinerários da assistência psiquiátrica em Cuiabá-MT na primeira metade do século XX - Pinho, Rachel Tegon de (2019)
The milestone in the process of institutionalizing assistance to the alienated in the State of Mato Grosso dates from 1915, with the inauguration of the Alienate Pavilion attached to the Santa Casa de Misericórdia de Cuiabá. It is said that this action aimed at the collection of the alienated from the capital of Mato Grosso, however, the unit would not be operational until 1929, however for a short period, since in 1931 the Coxipó da Ponte Alienate Asylum was established, located on the bank. to the left of the Coxipó River, about 10 km away from the Cuiabana capital and where the poor alienated people started to be collected. However, more than the slowness of this process, we are interested in understanding how it happened. Our investigative look is focused on the analysis of official documents, journals and intellectual articles, in the light of the concepts of hygiene, care, utopia, heterotopias, charity and philanthropy, as key to understanding this itinerary where infamous characters and figures are revealed, the light of Michel Foucault's concepts and historiographical productions that deal with these issues. We also use the presentation of unpublished documents that express the singularities of psychiatric care in Cuiabá in the first half of the twentieth century, as a hygiene strategy aimed at modernizing the capital and inserting the state of Mato Grosso in the nation building project.